Jovens de Gaza defendem que novo instrumento deve desburocratizar a obtenção de DUAT e combater a expropriação de terras pelas elites - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Falando em representação da Governadora da Província de Gaza, a Directora Provincial de Cultura e Turismo denunciou o velho problema de usurpação e acumulação de terra para fins de especulação latifundiária. Trata-se de uma prática comum em Moçambique em que as elites económicas e políticas se apropriam de terras valiosas e ficam à espera do melhor momento para fazer a transacção, preferencialmente com o capital estrangeiro. A representante da Governadora de Gaza disse que esta prática prejudica mais as mulheres que vivem nas zonas rurais por constituírem o grupo que mais usa a terra para a actividade agrícola. A Directora Provincial de Cultura e Turismo em Gaza saudou a iniciativa do CDD de auscultar a juventude sobre a revisão da Política Nacional de Terras, defendendo que, sendo a maioria da população, os jovens devem se apropriar do debate para influenciar a concepção de futuros instrumentos políticos e legais sobre o uso de terras.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; GP - Gaza; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra; youth / juventude

Jovens de Inhambane defendem que futura legislação deve estabelecer um prazo de até 15 dias para resposta ao pedido do DUAT - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Depois da cerimónia inaugural de quinta-feira na Província de Gaza, ontem, sexta-feira, 07 de Maio, foi a vez de Inhambane acolher o debate público no âmbito da auscultação de jovens sobre a revisão da Política Nacional de Terras. Falando na abertura da cerimónia, o Director dos Serviços Provinciais do Ambiente, em representação da Secretária de Estado da Província de Inhambane, defendeu que um dos desafios que a Inhambane enfrenta é o aumento do número de população perante um recurso terra que não é renovável, aliado aos desafios decorrentes das mudanças climáticas que demandam uma compensação da biodiversidade. O Director dos Serviços Provinciais do Ambiente de Inhambane falou também da emergência dos megaprojectos que, para o seu desenvolvimento, precisam do recurso terra. “A iniciativa do CDD de auscultar jovens sobre a revisão da Política Nacional de Terras constitui uma exaltação da cidadania. Todos nós, como moçambicanos, nas nossas comunidades, organizações, temos esta ímpar oportunidade de participar no melhoramento da nossa política de terras”.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; GP - Inhambane; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra; youth / juventude

Colateralização dos títulos de terra em Moçambique: bases para sua viabilização - Hamela, Hipólito; Macaringue, João; Rose, Ian (USAID, 2021)
No âmbito do processo de Revisão da Política Nacional de Terras e para responder aos consensus alcançados na IX Sessão do Forum de Consulta sobre as Terras (FCT) que incluiam a viabilização da transmissibilidade dos títulos de uso e aproveitamento da terra (DUAT) tornando este processo mais flexível, foi encomendado o presente estudo que tem como objectivo aferir, dentro do actual quadro legal, a viabilidade, sob o ponto de vista de oferta e da procura, da possibilidade de se implementar um programa de empréstimos, oferecendo como garantia, o DUAT. Do estudo resultará um ensaio piloto para testar os pressupostos que o estudo adopta como base, e que vão permitir a colateralização do direito de uso e aproveitamento da terra (DUAT) sem ferir os dispositivos legais vigentes. Também dele resulta a recomendação para a inclusão de elementos de clarificação no regulamento de terras o que tornará explícito que a colateralização do DUAT não é proibida. Para a realização deste trabalho foi feita uma revisão bibliográfica que incluiu os relatórios e declarações finais dos Foruns de Consulta sobre Terras, documentos do governo relativos à matéria de terras e estudos sobre a transmissibilidade dos títulos de uso e aproveitamento da terra. Também foi revista diversa legislação com impacto no uso e aproveitamento da terra com destaque para a Constituição da República, Lei e Regulamento de Terras, Código do Registo Predial e a legislação que cria a Central de Registo de Garantias Mobiliárias.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra

Guião metodológico para gestão de terras urbanas: gestão de terras urbanas municipais - República de Moçambique: Ministério do Meio Ambiente (República de Moçambique: Minitério da Terra e Ambiente, 2020)
O objectivo deste manual é auxiliar os municípios no contexto da gestão de terra, com especial foco na regularização do DUAT (Direito de Uso e Aproveitamento da Terra) e respectivas construções. O manual pretende abranger o maior número de situações que ocorrem no dia-a-dia, apresentando soluções apoiadas na presente legislação. Pretende-se que o manual seja um valioso material de apoio à capacitação das equipas técnicas dos municípios e áreas urbanas. O objectivo do manual é igualmente informar o público e capacitar os técnicos dos municípios e outras instituições com melhores técnicas e práticas para aperfeiçoar a gestão de terras de acordo com a legislação actual.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; governance / governação; land governance / gestão de terra; urbanization / urbanização

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Displacement and Dispossession Through Land Grabbing in Mozambique: The Limits of International and National Legal Instruments - Twomey, Hannah (Refugee Studies Centre (RSC), 2014)
This working paper examines the limitations of international and national law to address displacement and dispossession from land grabs within the case study of Mozambique. The main question that I seek to answer is: What limits international and national law in addressing displacement and dispossession due to land grabs in Mozambique? I will argue that the limits of law to address displacement and dispossession are not due to a lack of institutionalising international good governance norms into domestic-level legal frameworks. Nor can the limits be attributed to state incapacity. Rather, the limits of law lie within the norm implementation process, wherein norms are conditioned by the local Mozambican governance context to serve domestic interests
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; Law - Rule of Law / Law - Estado de Direito; governance / governação; land governance / gestão de terra

Guião de Consultas Comunitárias - Tankar, Issufo (Centro Terra Viva (CTV), 2014)
Em 2009, o Centro Terra Viva (CTV) publicou o Guião de Consultas Comunitárias, como parte do seu esforço em melhorar a aplicação da legislação sobre terras e outros recursos naturais. O guião resultou de várias pesquisas de campo realizadas pelo CTV e outras organizações que trabalham na área de Terras. No entanto, a aprovação do Decreto n° 43/2012 de 10 de Outubro, seguida do Diploma Ministerial n° 158/2011 de 15 de Junho, uma parte significativa do Guião ficou ultrapassada. Por outro lado, foram aprovadas directrizes pelo Fórum de Consulta sobre a Terra que são relacionadas a este tema. Deste modo, e como forma de facilitar a interpretação e aplicação do quadro legal sobre consultas comunitárias, o Centro Terra Viva, produziu este guião de consultas comunitárias destinado às comunidades, técnicos do Estado, técnicos de ONG’s e todos actores que trabalham na área de Terras.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Mozambique land policy development case study - Locke, Anna (Overseas Development Institute, 2014)
This case study has been produced in response to a request made to the Evidence on Demand Helpdesk. The objective of the request was to provide a detailed case study on the evolution of land policy in Mozambique and provide the reader with insights into what is viewed as one of Africa’s most progressive land laws, recognising multiple forms of tenure. Mozambique has experienced accelerated rates of growth over the past decade, averaging 7.2% per year, with projected growth rates of over 8%. However, this high growth rate has failed to translate into significant reductions in poverty and inequality has increased in almost all parts of the country. While growth has been driven by capital-intensive projects, mainly in the extractives sector, agriculture is seen as an important foundation for economic development and there has been a high level of interest in acquiring large tracts of land for investment over the past six years. Mozambique is one the most land-abundant countries in Africa, with around 80 million hectares (has). Currently, only five million hectares are cultivated, mainly by smallholders under rain-fed, traditional systems, and only 3-5% of landholdings are formally registered.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra

‘Operation of the Market's Study. How the poor access, hold and trade land: Findings from research in two settlements in Tete, Mozambique - Gordon, Ross; Taljaard, Reathe; Massuanganhe, Egildo, Egildo (Progressus Research Development Consultancy, 2013)
The way in which informal land transactions occur and the extent to which they result in tenure security and asset creation in these informal settlements is not well understood. For this reason this study comprises research into two informal settlements (namely Matundo and Mateus Sansão Muthemba [Sansão Muthemba]) in Tete, Mozambique, so as to understand how the poor access, hold and trade land. This research forms part of a larger research programme being undertaken by Urban LandMark which includes similar studies in Lilongwe (Malawi), Maputo (Mozambique), Luanda (Angola) and Durban, Cape Town and Johannesburg (South Africa). Reports on these other research projects can be seen on www.urbanlandmark.co.za.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; governance / governação; land governance / gestão de terra

Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude